A named General Practitioner (GP) is associated with an increase of hospital days in a single predictor analysis: a follow-up of 15 years - Emmi Lautamatti; Kari J. Mattila; Sakari Suominen; Lauri Sillanmäki; Markku Sumanen (BMC, 2023)
Abstract Background Continuity of care constitutes the basis of primary health care services and is associated with decreased hospitalization. In Finland, accessibility to primary care and increased use of hospital services are recognized challenges for the health care system. Objectives The aim of the study was to determine whether having a named GP is associated with hospital service use. Methods The data are part of the Health and Social Support study (HeSSup) based on a random Finnish working-age population sample. The cohort of the study comprised participants of postal surveys in 1998 (n = 25,898) who returned follow-up questionnaires both in 2003 and 2012 (n = 11,924). Background characteristics were inquired in the questionnaires, and hospitalization was derived from national registries (Hilmo-register). Results A named GP was reported both in 2003 and 2012 only by 34.3% of the participants. The association between hospital days and a named GP was linearly rising and statistically significant in a single predictor model. The strongest associations with hospital use were with health-related factors, and the association with a named GP was no longer significant in multinomial analysis. Conclusion A named GP is associated with an increased use of hospital days, but in a multinomial analysis the association disappeared. Health related factors showed the strongest association with hospital days. From the perspective of the on-going Finnish health and social services reform, continuity of care should be emphasized.